2021
DOI: 10.1155/2021/6674470
|View full text |Cite
|
Sign up to set email alerts
|

Study of Proton, Deuteron, and Triton at 54.4 GeV

Abstract: Transverse momentum spectra of proton, deuteron, and triton in gold-gold (Au-Au) collisions at 54.4 GeV are analyzed in different centrality bins by the blast wave model with Tsallis statistics. The model results are approximately in agreement with the experimental data measured by STAR Collaboration in special transverse momentum ranges. We extracted the kinetic freeze-out temperature, transverse flow velocity, and freeze-out volume from the transverse momentum spectra of the particles. It is observed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
2
13
2
Order By: Relevance
“…At the same time, a negative correlation between T 0 and β T will also be obtained. Thus, this situation is in agreement with some references [10,42,55,64,65], but if for central collisions, one even uses an almost unchanging or slightly larger T 0 and a properly larger β T , an almost invariant or slightly increasing trend for T 0 from peripheral to central collisions can be obtained [7,15,56,63]. In order to show the flexibility in the extraction of T 0 and β T , this work has reported a decreasing trend for T 0 from central to peripheral collisions, and a positive correlation between T 0 and β T .…”
Section: Resultssupporting
confidence: 93%
“…At the same time, a negative correlation between T 0 and β T will also be obtained. Thus, this situation is in agreement with some references [10,42,55,64,65], but if for central collisions, one even uses an almost unchanging or slightly larger T 0 and a properly larger β T , an almost invariant or slightly increasing trend for T 0 from peripheral to central collisions can be obtained [7,15,56,63]. In order to show the flexibility in the extraction of T 0 and β T , this work has reported a decreasing trend for T 0 from central to peripheral collisions, and a positive correlation between T 0 and β T .…”
Section: Resultssupporting
confidence: 93%
“…The difference in the two temperatures is due to the reason that they occur at two different process in the system evolution. Furthermore, it is also possible that the centrality dependence of the two types of temperatures is also different if one gets the increasing trend from central to peripheral for T 0 which is observed in our recent work [64,65]. In fact the trend dependence of T 0 is also an open question in high energy collisions because different literature give different trend.…”
Section: B Tendencies Of Parametersmentioning
confidence: 81%
“…We can use Equation (1) for the fitting of p T spectra and extract the parameters T 0 , β T , and V. Equation ( 1) is applicable in only the soft p T (p T = 2-3 GeV/c) regime of the p T spectra and is valid for a narrow p T range. In the range of p T >3 GeV/c, a hard scattering process should be brought into consideration, which was studied in our previous studies [5,8,9,13,16,18].…”
Section: Formalism and Methodsmentioning
confidence: 99%
“…In the literature, there are various kinetic freeze-out scenarios including single, double, triple, and multiple kinetic freeze-out scenarios [9][10][11][12][13][14]. In addition, there are various claims and dependencies of the kinetic freeze-out temperature on centrality [5][6][7][8][9][10]13,[15][16][17] and collision energy [2,3,10,18]. In our recent work, it was observed that the kinetic freeze-out temperature also depends on coalescence and isospin symmetry [19].…”
Section: Introductionmentioning
confidence: 99%